AB1323 Does obesity represent a risk factor for a poor remission rate in japanese patients with rheumatoid arthritis treated with anti-tumour necrosis factor-alpha therapy?. (12th June 2018) - Yamazaki, K.; Inoue, T.; Miyamoto, T.
Abstract : Background: Despite increased interest in the association between obesity and rheumatoid arthritis(, 1 evidence remains sparse in the Japanese population due to the fact that Asians have different associations between the body mass index (BMI), percentage of body fat, and health risks compared with the Western population. To address this problem, a World Health Organisation (WHO) consultation report proposed appropriate BMI cut-off points for the Asian population and redefined obesity as BMI of ≥27.5 kg/m 2 (. 2 Objectives: From the perspective of exploring the association of obesity and rheumatoid arthritis, it is necessary to precisely define obesity for appropriate ethnic groups. Hence, this study aimed to assess whether obesity represents a risk factor for a poor remission rate in Japanese patients with rheumatoid arthritis requiring anti-tumour necrosis factor-alpha (TNF-a) therapy using appropriate BMI cut-off points for the Asian population. Methods: Participants were identified from our hospital in Shizuoka, Japan, and followed up from 2009 to 2017. Based on WHO guidelines, we classified participants using an appropriate BMI for the Asian population as follows: underweight, <18.5 kg/m 2 ; normal weight, 18.5–23.0 kg/m 2 ; overweight, 23.0–27.5 kg/m 2 ; and obese, ≥27.5 kg/m 2 . The primary outcome was to define whether obesity affects the clinical response to anti-TNF-a therapy. The response variable was defined as the simplified disease activity index (SDAI) remission after 12 months. In addition, we estimated multivariate odds ratios and their 95% confidence intervals (CIs) for nonremission after 12 months of initiating anti-TNF-a therapy or censored as nonresponders to the therapy after adjusting for sex, age, smoking status, anticyclic citrullinated peptide antibody status, rheumatoid factor status, and disease duration. Results: We monitored 295 outpatients with rheumatoid arthritis who received anti-TNF-a therapy for at least 12 months or censored as nonresponders to the therapy. The mean ±SD for SDAI at the baseline was 24.20±14.47. The BMI was ≥27.5 kg/m 2 (obese) in 16 (4.2%) of 295 patients. At the 12 month follow-up, 62.0% of patients with rheumatoid arthritis had reached SDAI remission. The multivariate odds ratio for nonremission at 12 months or nonresponsiveness of obese patients referred to normal weight was 2.24 (0.53–9.43), which tended to be higher for poor response, albeit not significantly. Conclusions: Obesity may represent a risk factor for a poor remission rate in Japanese patients with rheumatoid arthritis treated with anti-TNF-a therapy. Thus, weight-loss programs might be a feasible solution for improving the condition of obese Japanese patients with rheumatoid arthritis. References: [1] Liu Y, Hazlewood GS, Kaplan GG, Eksteen B, Barnabe C. Impact of obesity on remission and disease activity in rheumatoid arthritis: a systematic review and meta-analysis. Arthritis Care Res (Hoboken). 2017Feb;69(2):157–65. [2] WHO Expert Consultation. Appropriate body-mass index for Asian populations and its implications for policy and intervention strategies. Lancet (London, England). 2004Jan;363(9403):157–63. Disclosure of Interest: None declared